Optimization of use conditions for cathodic arc nickel coating doped with phosphorus - Lapitskaya, V.A.; Kuznetsova, T.A.; Trukhan, R.E.; Khabarava, A.V.; Chizhik, S.A.; Kuprin, A.S.; Komarov, A.I. (Вопросы атомной науки и техники, 2021)
The results of tribological tests for a cathodic arc nickel coating doped with phosphorus are presented. The coating (thickness of 2 μm) is applied by a vacuum arc method from a nickel target with 6% phosphorus. The friction coefficient (Cfᵣ) was determined on the tribometer, the depth of wear h of the coating after tribological tests was determined by the contact profilometry method, and the specific volumetric wear (ω) was calculated. The obtained values of Cfᵣ, ω, and h were used to optimize the parameters of tribological tests (load and slip frequency). Представлено результати триботехнічних випробувань катодно-дугового нікелевого покриття, легованого фосфором. Покриття товщиною 2 мкм нанесено катодно-дуговим методом з нікелевої мішені з 6% фосфору. На трибометрі визначені коефіцієнти тертя (kтр), методом контактної профілометрії визначена глибина зносу (h) покриття після триботехнічних випробувань, розрахований питомий об'ємний знос (ω). За отриманими значеннями kтр, ω та h проведена оптимізація параметрів триботехнічних випробувань: навантаження та частоти ковзання. Представлены результаты триботехнических испытаний катодно-дугового никелевого покрытия, легированного фосфором. Покрытие толщиной 2 мкм нанесено вакуумно-дуговым методом из никелевой мишени с 6% фосфора. На трибометре определены коэффициенты трения (kтр), методом контактной профилометрии определена глубина износа (h) покрытия после триботехнических испытаний, рассчитан удельный объемный износ (ω). По полученным значениям kтр, ω и h проведена оптимизация параметров триботехнических испытаний: нагрузки и частоты скольжения.